Efeito da densidade de semeadura e de reguladores vegetais sobre os caracteres morfofisiológicos da folha bandeira do trigo - Fioreze, Samuel L. [UNESP]; Rodrigues, João Domingos [UNESP] (Revista Brasileira de Ciencias Agrarias, 2012)
The objective of this work was to study the morphological and physiological characteristics of the wheat flag leaf as affected by increasing sowing densities and plant growth regulators application. The experimental design was a split-plot with completely randomized blocks and four replications. Plots were consisted by four sowing densities (30, 50 70 and 90 plants m-1) and the split-plots by plant growth regulators: a product composed by auxin+gebberellin+cytokinin (Ax+GA+CK), Trinexapac-Ethyl e (Ax+GA+CK) + Trinexapac-Ethyl, and a control without application. Dry mass accumulation, plant height, morphological characteristics, SPAD index, nitrogen and photosynthetic pigments contents in the flag leaf were determined. The increase in the sowing density resulted in lower dry mass accumulation and SPAD index of the flag leaves. Trinexapac-Ethyl caused increase in the SPAD index, but the chlorophyll content of the flag leaf was reduced. The SPAD index values were more correlated with the nitrogen than the chlorophyll contents. Ax+GA+CK did not affect flag leaf characteristics in wheat plants.
Effects of sowing density and plant growth regulators on the morphological and physiological characteristics of the wheat flag leaf
Keywords: Auxin; Chlorophyll; Cytokinin; Gibberellin; Nitrogen; SPAD index; Trinexapac-Ethyl; Triticum aestivum